2013
DOI: 10.1111/pbr.12030
|View full text |Cite
|
Sign up to set email alerts
|

Converting restriction fragment length polymorphism to single‐strand conformation polymorphism markers and its application in the fine mapping of a trichome gene in cotton

Abstract: A well‐characterized and systematically organized collection of genetic markers is crucial in the study of any crop species. It is the basis of map‐based gene cloning and crop improvements through marker‐assisted selections. Single‐strand conformation polymorphism (SSCP) has been a robust way of discovering new polymorphisms in marker development without the requirement of sequencing. Here, we report the first approach of applying SSCP marker discovery methods in the genetic map construction and gene mapping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This trait cosegregates with the loss-of-fiber mutant sma-4 (Desai et al 2008;He et al 2013). Recently, map-based cloning of sma-4 was conducted by our research group using a large-scale high-resolution finemapping population containing 2500+ individuals, which suggested strongly that the underlying causative gene for the sma-4 phenotype is HD1 on chromosome LG A03.…”
Section: Trichome Phenotypes In G Barbadensementioning
confidence: 98%
See 4 more Smart Citations
“…This trait cosegregates with the loss-of-fiber mutant sma-4 (Desai et al 2008;He et al 2013). Recently, map-based cloning of sma-4 was conducted by our research group using a large-scale high-resolution finemapping population containing 2500+ individuals, which suggested strongly that the underlying causative gene for the sma-4 phenotype is HD1 on chromosome LG A03.…”
Section: Trichome Phenotypes In G Barbadensementioning
confidence: 98%
“…Genetic marker candidates that are potentially linked to trichome phenotypes were chosen from both published A genome (He et al 2013) and tetraploid genome mapping studies (Wright et al 1999;Rong et al 2007). Candidate RFLP markers were screened for polymorphisms between the parents of the mapping population in this study (T586 and Pima S6), as reported by He et al (2013).…”
Section: Marker Development and Dna Extractionmentioning
confidence: 99%
See 3 more Smart Citations